Kursus falsafah dan isu semasa sebagai alat pembinaan identiti nasional: satu analisis literatur - Jahidih Saili, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Philosophy and Current Issues (FIS) course plays a crucial role as a tool for building national identity among students in Malaysian higher education institutions. However, the effectiveness of this course in achieving its objectives has not been thoroughly investigated. This study aims to evaluate the role of the FIS course in constructing national identity by analysing the curriculum content, teaching and learning approaches, and assessment methods employed in the course. Through the document analysis method, materials related to the FIS course at selected universities are examined. The findings indicate that the FIS course successfully enhances students' understanding and appreciation of essential elements in the formation of national identity, such as history, the constitution, and national policies. The course is also found to be effective in cultivating a spirit of patriotism, strengthening unity, and fostering an attitude of appreciating the diversity of Malaysia's multi-ethnic society. The implications of this study highlight the potential of the FIS course in producing graduates with a strong sense of national identity who are capable of contributing to the overall development of the nation.